Implementation of Environmental Sanitation and Occupational Health Protection for Catfish Hatchery Workers in Sidomukti Village,West Kisaran District, Asahan Regency (JURNAL PENGMAS KESTRA (JPK), 2025)
Background: Aquaculture is a strategic sector with significant potential to support Indonesia’s economic growth. Its development is highly dependent on hatchery quality, as hatchery activities represent the initial stage that determines production success. High-quality hatcheries, both in terms of seed quantity and quality, are essential for sustainable aquaculture development. Moreover, aquaculture activities are closely associated with proper environmental sanitation and the protection of workers’ health. Objective: This program aimed to improve capacity and provide education for the community, particularly catfish hatchery workers, in order to enhance production quality and produce healthier, higher-quality catfish. Methodology: A participatory approach was implemented through group and individual activities. Assistance and coordination with partners were carried out through training sessions using lectures, discussions, regular monitoring, and hands-on practice on the application of proper environmental sanitation in catfish production, as well as occupational health and safety measures for workers. Monitoring was conducted monthly or adjusted to partners’ needs, accompanied by continuous motivation and information sharing to promote a clean and healthy production environment. Results: The program led to increased environmentally friendly catfish farming productivity, improved community health status, enhanced hatchery skills among participants, and the availability of wastewater treatment facilities and occupational health and safety infrastructure. Conclusion: The community service program produced tangible benefits for partner groups, including more regular and well-planned catfish hatchery operations, increased seed production, and reduced technical risks. In addition, it fostered a strong awareness and culture of occupational health and safety and created a more conducive aquaculture environment that is cleaner and free from pollutants and ammonia odors through the application of environmental sanitation principles.